2010
DOI: 10.1089/end.2009.0233
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Efficacy of Dilatation Therapy Combined with Steroid After Internal Urethrotomy in the Management of Urethral Stenoses

Abstract: As an adjuvant treatment, this method is effortless, low in complications, and hopeful. Certainly, application to larger patient populations is needed to objectively accept its efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
21
0
2
Order By: Relevance
“…Etiologic factors for urethral stricture disease include perineal trauma, urethral catheterization, urologic instrumentation, chronic inflammatory diseases such as lichen sclerosus, and sexually transmitted diseases. However, most cases of urethral strictures are idiopathic, and most patients probably have unrecognized childhood trauma [6]. The first identifiable change in urethral stricture disease is a change in the nature of the urethral epithelium from a pseudo-stratified columnar epithelium to a columnar epithelium that lacks the waterproofing quality of the pseudo-stratified variant.…”
Section: Discussionmentioning
confidence: 99%
“…Etiologic factors for urethral stricture disease include perineal trauma, urethral catheterization, urologic instrumentation, chronic inflammatory diseases such as lichen sclerosus, and sexually transmitted diseases. However, most cases of urethral strictures are idiopathic, and most patients probably have unrecognized childhood trauma [6]. The first identifiable change in urethral stricture disease is a change in the nature of the urethral epithelium from a pseudo-stratified columnar epithelium to a columnar epithelium that lacks the waterproofing quality of the pseudo-stratified variant.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, improvements in endoscopic surgery have contributed to the success rate of urethral stricture surgery [10,11,16-18]. Triamcinolone, mitomycin-C, transforming growth factor beta oligodeoxynucleotide, and gene therapy-such as recombinant adenovirus and retrovirus gene transfer-have also been used as adjuvant treatment [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Gücük et al used a steroid-coated (triamcinolone acetonide 1%) 18 F hydrophilic dilatation catheter in post-VIU patients [10]. The steroids, which induce a fibroblast reaction, suppressed (experimentally and clinically) a decrease in the accumulation of collagen fibers and fibroblasts and inhibited the proliferation of fibroblasts in wound tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Gücük et al (19) reported that although there was no statistically significant difference in patients who retained the 18 Fr steroid-coated hydrophilic catheters for 2 weeks after internal urethrotomy, there was some increase in the operative maximum flow rate. Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…In this study where we did not find a significant difference, we also recommend to not prolong the postoperative urinary catheterization time and to remove it as quickly as possible. We recommend that the probe duration be at least 3 days due to the poor comfort it provides to the patient as well as the increased risk of infection as previously mentioned in the literature because a long postoperative urinary catheter time may lead to the emergence of recurrent stenosis, thus causing ischemic damage in the urethral mucosa (19). We also suggest that the urinary catheter time can be kept longer relying on the surgeon's experience in stenoses longer than 1 cm and traumatic stenoses that require recurrent urethrotomies.…”
Section: Urinarymentioning
confidence: 97%